EKSPRESI GEN PENYANDI b-XILOSIDASE DALAM SISTEM pHIS1525/ Bacillus megaterium MS941 - Sri Sumarsih; Ni Nyoman Tri Puspaningsih; Sofijan Hadi; Ami Soewandi J.S. (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2008)
The aim of this research was to express the β-xylosidase gene in the pHIS1525/ Bacillus megaterium MS941 system. The xyl gene was amplified from pTP510 and cloned into pHIS1525 in E. coli DH10β. The recombinant plasmid was transformed into B. megaterium MS941 by protoplast transformation. Transformants were selected by growing the recombinant B. megaterium MS941 on solid LB medium containing tetracycline (10 μg/ ml). The expression of β-xylosidase was assayed using 0.2% methylumbelliferyl-β-D-xyloside (MUX) and the proteins were analyzed by SDS-PAGE method. The β-xilosidase activity was determined toward p-nitrophenyl-β-Dxylopyranoside (pNPX) as a substrate and p-nitrofenol releasing was measured by UV/Vis spectrophotometer at λ = 405 nm. This research showed that recombinant B. megaterium MS941 expressed the β-xylosidase gene (xyl) and secreted it into the culture medium. The SDS-PAGE analysis of extracellular protein (culture medium) showed a 60,0 kD protein band. The recombinant Bacillus megaterium MS941 expressed and secreted the β-xilosidase into culture medium 5 hours after adding 5% xylose. The b-xylosidase activity was 0.441 unit/ml toward pNPX as a substrate.